PENGARUH FINANCIAL KNOWLEDGE, FINANCIAL ATTITUDE DAN LOCUS OF CONTROL TERHADAP FINANCIAL BEHAVIOR PADA PEDAGANG DIPASAR WAGE DUKUN GRESIK - Nur Anifah; Rahmat Agus Santoso (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
This research is motivated by the community, especially traders in the Wage Dukun Gresik market regarding consumptive financial behavior that tends to change. Traders today are becoming very consumptive of whatever they see without seeing that it is a need or just a desire. This study aims to explain the influence of financial knowledge, financial attitude and locus of control on financial behavior of traders in the Dukun Gresik wage market. This research is a research with a quantitative approach. The location of this research is the Dukun Gresik wage market. The variables in this study are financial knowledge, financial attitude, locus of control. The population in this research is the traders of the wage market of Dukun Gresik. The sample in this study is as many as 200 traders of the wage market of Dukun Gresik. The sampling technique is the Nonprobability Sampling or Incidental Sampling technique. The data collection technique used is by distributing questionnaires. The data analysis technique used multiple linear regression analysis techniques. The results of the study indicate that financial knowledge has a positive and significant effect on financial behavior in traders in the Dukun Gresik wage market. Financial attitude has a negative and insignificant effect on financial behavior of traders in the Dukun Gresik wage market. Locus of control has a positive and significant effect on financial behavior of traders in the Gresik shaman wage market.